ADMINISTRATIVE APPLICATIONS ANEKA D PARK READING USING VISUAL BASIC 6.0 - Guruh Edi Putra (Jurnal Sistem Informasi, 2006)
In this paper the author tries to help Aneka D Reading Park in making lending services, data storage of books, and members can also view the report, by creating a database application. It is expected that these applications can speed up service and reduce use of paper. Storing the data is stored with the media hard disk as a storage file so the reduced use of paper so it does not require more storage space and can find data quickly and efficiently as well as lending transaction records. Statements in this application can display the necessary data as all data books, data members, and lending transactions. With this report is expected to provide accurate and timely information to administrators Aneka D.